Monensin levels in a steam-flaked milo finishing diet with 4% added fat - Brandt, Robert T., Jr.; Anderson, S.J.; Elliott, J.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Response to monensin (Control, 12.5, or 25 g/ton, air dry basis) by yearling steers fed a diet with 4% added fat was evaluated. For the entire study (104 d), daily gain, feed consumption and feed efficiency were unaffected (P>.25) by monensin. These results are in general agreement with some of our previous reports of diminished animal response to ionophores in fat-supplemented finishing diets. No adverse effects on animal health have been observed in our studies. However, whether withdrawing ionophores from finishing rations with 3.5-4% fat will affect the incidence of digestive upsets in commercial applications is not clear.
Keywords: Beef; Monensin level; Fat; Cattle; Feedlot performance